Biological Parameters of Blacksaddled Coralgrouper (Plectropomus laevis Lacepède, 1801) Eggs and Larvae - Regina Melianawati; Bejo Slamet (Marine Science Department Diponegoro University, 2019)
Blacksaddled coralgrouper, Plectropomus laevis, is an endangered species of marine fish. As part of conserving their existence in the wild, culture of this species has been started. However, knowledge of biological parameters of this species as important indicators to observe the fish growth in mariculture scale, is limited. The purpose of this study was to observe biological parameters during eggs, larval to juvenile stage of blacksaddled coralgrouper in mariculture hatchery. The eggs were obtained from natural spawning of domesticated broodstocks. Larvae rearing was done in hatchery at three different times as replicates. Larval were fed with zooplankton which consist of rotifers Brachionus sp., wild copepods and Artemia. Artificial feed was also given to the fish larvae. Larval samples were taken one Day After Hatching (DAH), then continued every 5 days started at 5 to 45 DAH by using five larvae each sampling time. The observed parameters were diameter of eggs and oil globule, total length and standard length of larvae length of dorsal and pelvic fin spines of larvae. Furthermore, growth pattern of those length parameters was analysed by regression equation. The result showed that diameter of blacksaddled coralgrouper eggs was 835.19±15.29 µm, while oil globule was 177.78±10.30 µm. The growth patterns of larval total length and standard length were exponential, while dorsal and pelvic fin spines were polynomial. The length of time from larvae to achieve juvenile stage was range between 45-50 days. All of these information can be used as references either in larvae rearing or for further study of the fish.